Mechanism and Intervention of Pyroptosis Involved in Reperfusion Injury in Acute Coronary Syndrome - Liu, Rong; Sang, Zhiyang; Shen, Le (Journal of Contemporary Medical Practice, 2025)
Opening occluded blood vessels to achieve myocardial reperfusion is the most critical treatment for acute coronary syndromes, but with the return of blood, the heart tissue produces a strong stress response, and the infarction may be expanded or the heart function may be reimpaired, which is called myocardial ischemia reperfusion injury (MIRI). As a programmed cell death mode, pyroptosis has been widely confirmed to be involved in the MIRI process, and the main morphological characteristics are the formation of cell membrane pores of about 10~20nm, cell swelling accompanied by plasma membrane rupture, and the release of cell contents. In this article, we will review the mechanism of pyroptosis in MIRI and the intervention of various drugs in the pyroptosis pathway, so as to provide new ideas for exploring and improving MIRI.